2016
DOI: 10.1186/s12917-017-0980-0
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of adipose-derived canine mesenchymal stem cells after superparamagnetic iron oxide nanoparticles labelling for magnetic resonance imaging

Abstract: BackgroundTherapy with mesenchymal stem cells (MSCs) has been reported to provide beneficial effects in the treatment of neurological and orthopaedic disorders in dogs. The exact mechanism of action is poorly understood. Magnetic resonance imaging (MRI) gives the opportunity to observe MSCs after clinical administration. To visualise MSCs with the help of MRI, labelling with an MRI contrast agent is necessary. However, it must be clarified whether there is any negative influence on cell function and viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
0
20
1
1
Order By: Relevance
“…Previous studies have shown that labelling cells with iron oxide nanoparticles can inhibit differentiation to specific lineages [22,23]. In our study, we did not find any evidence that the bicistronic Fluc-ZsGreen reporter or the MPIOs inhibited the differentiation of hESC-derived DAPCs into TH + DA neurons.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies have shown that labelling cells with iron oxide nanoparticles can inhibit differentiation to specific lineages [22,23]. In our study, we did not find any evidence that the bicistronic Fluc-ZsGreen reporter or the MPIOs inhibited the differentiation of hESC-derived DAPCs into TH + DA neurons.…”
Section: Discussioncontrasting
confidence: 81%
“…Canine adipose-derived stem cells were incubated with superparamagnetic iron oxide nanoparticles (SPIO: 319.2 μg/mL Fe) for 24 h. The iron oxide nanoparticles enter into the cells via endocytosis. Further the results showed there is no significant harmful effect on the viability of adipose-derived canine mesenchymal stem cells; therefore, it can be used for as contrast agent [ 156 ]. Long et al reported that ultra-small superparamagnetic iron oxide nanoparticles used as MRI tracking agent to measure the seizure disorders in a rat model of temporal lobe epilepsy [ 157 ].…”
Section: Types Of Various Nanomaterials Used In Veterinary Medicinmentioning
confidence: 99%
“…(2) PLGA/IO MPs (PLL) was able to label TSCs and these labeled cells could be noninvasively monitored by both MRI and PA imaging for 21 days and 7 days respectively in rat rotator cuff injury model; (3) The therapeutic capacity of TSCs was not affected by PLGA/IO MPs labeling in a rat model of rotator cuff injury. As we known, iron oxide nanoparticles (IO NPs) like superparamagnetic iron oxide (SPIO) have been extensively used as contrast agents for MR tracking because of their favorable biocompatibility and the high sensitivity in T2*-weighted images 17,[28][29][30][31] . The sensitivity is dependent on the IO NPs loading of the cell as well as the density of labeled cells in an imaging voxel 32 .…”
Section: Discussionmentioning
confidence: 99%
“…As we known, iron oxide nanoparticles (IO NPs) like superparamagnetic iron oxide (SPIO) have been extensively used as contrast agents for MR tracking because of their favorable biocompatibility and the high sensitivity in T2*-weighted images 17 , 28 31 . The sensitivity is dependent on the IO NPs loading of the cell as well as the density of labeled cells in an imaging voxel 32 .…”
Section: Discussionmentioning
confidence: 99%